Low oxalobacter formigenes colonization is associated with reduced bone mineral density in urinary stone forming patients - Pençe, Sadrettin; İkizceli, İbrahim; Özbek, Emin; Tiryakioğlu, Necip Ozan; Eren, Hilal; Polat, Emre Can; Pençe, Halime Hanım (S. Karger AG, 2014)
Introduction: Lower bone mineral density (BMD) and reduced Oxalobacter formigenes colonization are common findings in urolithiasis patients. But none of the studies conducted investigated the relationship between decreased bone mineral density and reduced Oxalobacter colonization. Here we evaluated the relation between BMD and O. formigenes colonization in urolithiasis patients. Materials and Methods: 50 stone formers (48.9 ± 11.9 years) and 50 control (47.2 ± 13.4 years) adult male subjects were included in the study. Alterations in O. formigenes colonization were determined as absolute O. formigenes count from fecal samples by real time polymerase chain reaction using species specific primers. BMD was evaluated from t- and z- scores calculated by using dual energy absorptiometry in the total femoral neck and lumbar spine (L2-L4). Results: Low BMD was observed in 18 (36%) urinary stone forming patients and in 7 (14%) control subjects in the lumbar area (p < 0.05). The mean O. formigenes count in stone formers and control subjects were 19,257 (5,791 ± 1,117.93) and 143,850 (2,815,725 ± 3,946,044.7) (p < 0.05) respectively. We observed a correlation between decreased lumbar BMD and O. formigenes colonization and testosterone levels in stone formers. Our results indicated that diminished O. formigenes colonization in the gut of urinary stone forming subjects was associated with reduced BMD.
Keywords: Bone Mineral Density; Oxalate Degradation; Oxalobacter Formigenes; Urolithiasis